GREEN INNOVATION AND MARKETING STRATEGIES: A SUSTAINABILITY-ORIENTED BIBLIOMETRIC ANALYSIS - Zulkieflimansyah, Zulkieflimansyah; Khadafie, Muammar (Jurnal Ekonomi dan Bisnis Indonesia, 2025)
Green marketing has emerged as a pivotal corporate sustainability and innovation strategy, influencing business performance, regulatory policies, tourism, and consumer behaviour. Companies increasingly integrate eco-friendly marketing approaches to enhance competitiveness, comply with regulations, and appeal to environmentally conscious consumers. Research highlights that green marketing fosters innovation strengthens corporate environmental commitments, and improves sustainability outcomes. Studies show businesses investing in sustainable branding, supply chains, and product development experience long-term profitability and resilience. Consumer trust is crucial in green marketing effectiveness, with transparent environmental labelling and ethical business practices driving customer loyalty. However, deceptive sustainability claims, or "greenwashing," pose reputational risks, emphasizing the need for authenticity in sustainability initiatives.